Impact of Urbanization on Energy Intensity in Indonesia: Spatial Analysis - Herry Irawan; Djoni Hartono (Jurnal Perencanaan Pembangunan: The Indonesian Journal of Development Planning, 2022)
Urbanization is a phenomenon in developing countries that needs to be studied in depth because it has various impacts, including an increase in energy consumption. Energy consumption needs to be controlled to balance energy supply and demand in each province. In this study, energy intensity will be used to measure energy consumption, and regional elements are used to capture the diversity of characteristics in each province. The purpose of this study is to 1) Is there a spatial correlation in energy intensity in Indonesia; and 2) What is the spatial (direct, indirect, and total) impact of urbanization on energy intensity in the Indonesian region, Eastern Indonesia Region (KTI), and Western Indonesia Region (KBI). The research method used is a spatial analysis using Moran Test, Spatial Durbin Model, and advanced decomposition analysis on the spatial spillover effect. The result is a spatial correlation to the energy intensity that occurs in each province. Urbanization shows a significant negative impact on energy intensity on the direct effect on KTI and KBI and also on the indirect effect and the total effect in the territory of Indonesia and KBI.